ANALISIS NIAI TAMBAH KERIPIK KENTANG DAGING (KRITING) VARIAN PEDAS - Nurhana Jafaruddin (Universitas Galuh Ciamis, 2021)
The purpose of this research is to know the process of meat potato chips processing (kriting) variant spicy and the value added was obtained on the processing of meat potato chips variant spicy. The research location was chosen purposively, using the case study method. This study uses the Hayami method analysis. The results obtained are the processing of meat potato chips (kriting) using semi-modern techniques that include potato stripping, potato shrinkage, leaching and potato drying, potato frying, the addition of meat as a mixture of potato chips, the production of potato chips with meat flavor, mixing potato chips and meat with seasoning.The value added was obtained from the process of potatoes into meat potato chips (kriting) variant spycy is Rp. 70,000.45 per kilogram. Value-added ratio is 44.16 percent with conversion factor of 0.518 and labor coefficient of 0.35 JKO. The rate of profit earned by employers is 84.48 percent. Output value is Rp. 135,136,00per kilogram.